Osteokondroma pada Tibia Proksimal pada Seorang Anak Laki-laki Berusia 12 Tahun: Laporan Kasus: Laporan Kasus - Prawiragara, Fachrizal Arfani; Tedjaprasadja, Leonardo (Cermin Dunia Kedokteran, 2026)
Introduction: Osteochondroma is the most common benign bone tumor, commonly occurring in the metaphyseal region of long bones during the second and third decades of life. Although frequently asymptomatic, osteochondroma arising from the proximal tibia in a skeletally immature patient is uncommon and may present challenges due to its proximity to the growth plate. This case highlights the diagnostic and surgical considerations in pediatric patient required to preserve skeletal growth while achieving complete tumor removal. Case: A 12-yearold boy presented with a painless swelling over the proximal region of the right tibia that had progressively developed over two months. Physical examination revealed a firm, immobile bony mass measuring approximately 2 × 2.5 cm, no tenderness and without neurovascular impairment. Radiographic evaluation demonstrated a pedunculated osteochondroma with continuity of the cortex and medulla with the host bone, showing growth away from the epiphysis and a positive neck sign. Surgical excision was performed with careful preservation of surrounding neurovascular structures. Histopathological examination confirmed the diagnosis of conventional osteochondroma without malignant features. Conclusion: This case represents an uncommon presentation of proximal tibial osteochondroma in a skeletally immature patient. Early recognition, appropriate imaging assessment, and meticulous surgical planning are essential to prevent complications and maintain normal limb function. At follow-up, the patient showed no recurrence and returned to normal activities.